Nanobiotechnological basis of an oxygen carrier with enhanced carbonic anhydrase for CO2 transport and enhanced catalase and superoxide dismutase for antioxidant function - Bian, Yuzhu; Chang, Thomas Ming Swi (Frontiers in Bioengineering and Biotechnology, 2023)
This is a mini review on the biotechnological aspects of the most extensively developed hemoglobin-based oxygen carriers (HBOCs). The emphasis is on the most recent Polyhemoglobin-catalase-superoxide dismutase-carbonic anhydrase (PolyHb-CAT-SOD-CA) which is a nanobiotecnological complex that is being investigated and scale up with the potential for clinical use as nanobiotherapeutics. Hemoglobin, a tetramer, is an excellent oxygen carrier. However, in the body it is converted into toxic dimers. Diacid or glutaraldehyde can crosslink hemoglobin into polyhemoglobin (PolyHb) and prevent its breakdown into toxic dimers. This has been developed and tested in clinical trials. A bovine polyhemoglobin has been approved for routine clinical use for surgical procedures in South Africa and Russia. Clinical trials with human PolyHb in hemorrhagic shock was effective but with a very slight increase in nonfatal myocardial ischemia. This could be due to a number of reasons. For those conditions with ischemia-reperfusion one would need an oxygen carrier with antioxidant properties. One approach is to prepared polyhemoglobin-catalase-superoxide dismutase (PolyHb-CAT-SOD). Another reason is an increase in intracellular pCO2. We therefore added an enhanced level of carbonic anhydrase (CA) to prepare a PolyHb-CAT-SOD-CA. The result is an oxygen carrier with enhanced Carbonic Anhydrase for CO2 transport and enhanced Catalase and Superoxide Dismutase for antioxidant functions. Detailed efficacy and safety studies have led to the industrial scale up towards clinical trial. In the meantime, oxygen carriers are being investigated around the world for use in ex vivo biotechnological fluid for organ preservation for transplantation with one already approved in France.